Gene Avatars The Neo-Darwinian Theory of Evolution - Gouyon, Pierre-Henri. (Springer US, 2002)
`Why life?' Questions of this type were for a long time the prerogative of philosophers who left the `how' question to scientists. Nowadays, Darwin's successors no longer have any qualms about addressing the `why' as well as the `how'. Over a century ago, Darwin modestly admitted having 'thrown some light on the origin of species - this mystery of mysteries'. Two major advances in the following decades helped biologists answer many of the questions he left unsolved. The first was the discovery of the laws of heredity, the second that of DNA. Both provided Darwinian theory with the foundations that were lacking and led to the all-embracing neo-Darwinian synthesis. Since then, Theodosius Dobzhansky's aphorism `nothing in biology makes sense except in the light of evolution' has proven true more than once. This does not suit everyone, as evolutionist ideas have not lost their power to cause a scandal. Darwin toppled man from his pedestal. Evolutionary genetics - the subject of this book - sends the individual crashing. Considered until recently to be the target of selection and the focus of evolution, the individual has been usurped by the gene. The individual is nothing but the gene's avatar.